Stranded false killer whales, Pseudorca crassidens, in Southern South America reveal potentially dangerous silver concentrations - Cáceres Saez, Iris; Haro, Daniela; Blank, Olivia; Aguayo Lobo, Anelio; Dougnac, Catherine; Arredondo, Cristóbal; Cappozzo, Humberto Luis; Ribeiro Guevara, Sergio (Marine Pollution Bulletin)
Silver (Ag) is a non-essential metal known to bioaccumulate in aquatic organisms. We determined Ag concentrations in five false killer whales stranded in South America. Silver concentrations (in dry weight basis) range as 6.62–10.78 μg g−1 in liver, 0.008–7.41 μg g−1 in spleen, 0.004–5.71 μg g−1 in testis, 0.757–1.69 μg g−1 in kidney, 0.011–0.078 μg g−1 in lung and < 0.01–0.038 μg g−1 in muscle, whereas in the single samples of uterus and ovary were 0.051 and 0.023 μg g−1; respectively. Overall, Ag concentration in liver and kidney exceeded the cetacean toxic thresholds, proposed as “unhealthy concentrations” and “critically dangerous” in liver and kidney. These results warrant further eco-toxicological studies, to examine biological effects of elevated silver levels for individuals and to assess the species' conservation status with respect to marine pollution. Fil: Cáceres Saez, Iris. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Haro, Daniela. Universidad Santo Tomás. Centro Bahía Lomas; Chile Fil: Blank, Olivia. Clínica Veterinaria Timaukel; Chile Fil: Aguayo Lobo, Anelio. Instituto Antártico Chileno; Chile Fil: Dougnac, Catherine. Universidad de Chile; Chile Fil: Arredondo, Cristóbal. Tarukari; Chile Fil: Cappozzo, Humberto Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Ribeiro Guevara, Sergio. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Unidad de Actividad de Ingeniería Nuclear. Laboratorio de Análisis por Activación Neutrónica; Argentina